Immune correlates of protection by vaccine against SARS‐CoV‐2 in patients with chronic lymphocytic leukaemia. (9th December 2022) - Sorcini, Daniele; De Falco, Filomena; Gargaro, Marco; Bozza, Silvia; Guarente, Valerio; Cardinali, Valeria; Stella, Arianna; Adamo, Francesco Maria; Silva Barcelos, Estevao Carlos; Rompietti, Chiara; Dorillo, Erica; Geraci, Clelia; et al.
Summary: In chronic lymphocytic leukaemia (CLL) the efficacy of SARS‐CoV‐2 vaccination remains unclear as most studies have focused on humoral responses. Here we comprehensively examined humoral and cellular responses to vaccine in CLL patients. Seroconversion was observed in 55.2% of CLL with lower rate and antibody titres in treated patients. T‐cell responses were detected in a significant fraction of patients. CD4 + and CD8 + frequencies were significantly increased independent of serology with higher levels of CD4 + cells in patients under a Bruton tyrosine kinase (BTK) or a B‐cell lymphoma 2 (BCL‐2) inhibitor. Vaccination skewed CD8 + cells towards a highly cytotoxic phenotype, more pronounced in seroconverted patients. A high proportion of patients showed spike‐specific CD4 + and CD8 + cells producing interferon gamma (IFNγ) and tumour necrosis factor alpha (TNFα). Patients under a BTK inhibitor showed increased production of IFNγ and TNFα by CD4 + cells. Vaccination induced a Th1 polarization reverting the Th2 CLL T‐cell profile in the majority of patients with lower IL‐4 production in untreated and BTK‐inhibitor‐treated patients. Such robust T‐cell responses may have contributed to remarkable protection against hospitalization and death in a cohort of 540 patients. Combining T‐cell metrics with seroprevalence may yield a more accurate measure of population immunity in CLL, providing consequential insights for public health.